Assessing the relative importance of neutral stochasticity in ecological communities - Vellend, Mark; Srivastava, Diane S.; Anderson, Kathryn M.; Brown, Carissa D.; Jankowski, Jill E.; Kleynhans, Elizabeth J.; Kraft, Nathan J. B.; Letaw, Alathea D.; Macdonald, A. Andrew M.; Maclean, Janet E.; Myers-Smith, Isla H.; Norris, Andrea R.; et al. (Oikos, 2014)
A central current debate in community ecology concerns the relative importance of deterministic versus stochastic processes underlying community structure. However, the concept of stochasticity presents several profound philosophical, theoretical and empirical challenges, which we address here. The philosophical argument that nothing in nature is truly stochastic can be met with the following operational concept of neutral stochasticity in community ecology: change in the composition of a community (i.e. community dynamics) is neutrally stochastic to the degree that individual demographic events – birth, death, immigration, emigration – which cause such changes occur at random with respect to species identities. Empirical methods for identifying the stochastic component of community dynamics or structure include null models and multivariate statistics on observational species-by-site data (with or without environmental or trait data), and experimental manipulations of 'stochastic' species colonization order or relative densities and frequencies of competing species. We identify the fundamental limitations of each method with respect to its ability to allow inferences about stochastic community processes. Critical future needs include greater precision in articulating the link between results and ecological inferences, a comprehensive theoretical assessment of the interpretation of statistical analyses of observational data, and experiments focusing on community size and on natural variation in species colonization order.